ASPEK TINJAUAN HUKUM PERANAN BANK INDONESIA DALAM MEMBERIKAN PERLINDUNGAN HUKUM NASABAH KARTU KREDIT TERHADAP DEBT COLLECTOR - Budiharto, Hendro Saptono, Muhammad Faisol Faizin (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The advance in technology and trade has brought a change in people’s need for a payment system that can meet the speed, accuracy, and security in every electronic transaction. The use of credit card as the payment instrument offer various easiness and advantages, such as more practical, safe, comfortable, and can utilize the credit facility given. In addition, it also reflects particular social status for the holders. Credit card developsrapidly, but it is in contrary with the enormous complaints from people who use the bank services including in Bank of Indonesia starting from the banking products until the services. One of the prominent complaints frequently exposed in mass media is about the credit collection to the use of credit card. Credit card holders are always in weak position to several harmful threats of risks to them. Here, the role of BI (Bank of Indonesia), as the authorized institution in payment system, is required in supervising the rapid growth of credit card with all their authority in the field of regulating, licensing, and supervising, to the implementation of credit card. The aspects that get attention from BI are the aspects of prudential, customer’s legal protection, and risk management of lending described in PBI (Peraturan Bank Indonesia) and SEBI (Surat Edaran Bank Indonesia)as the rules and legal review to the implementation of APMK (Alat Pembayaran Menggunakan Kartu). In addition, the sinergy of parties from customers, issuers, and organizers of APMK having good will understand the requirements determined and their obediences to the rules applied. If they can create it, the development of credit card will be healthy and accelerate the national economic growth. The aims of this research are to find out how the updated BI regulations in the supervising function tighten credit card issuance, the position and Legal Rules of Debt Collectors in Positive Law Perspective in Indonesia, the roles of BI in providing legal protection to credit card holder against debt collectors, and the regulations development in PBI and SEBI on APMK and Debt Collector. Theapproach method applied in this research was the legal approach method of normative juridical with the specification of analytical descripstive. The samples were taken by non-random purposive sampling. The data collected in the research consisted of primary data from the research in the field and secondary data as the theoretical basis. The results were analyzed using qualitative approach, that is , by composing the data obtained systematically, then the conclusion was drawn to answer the problems examined. On the basis of the research, BI has the role in controlling credit card issuance, licensing, reporting, impositioning sanctions to APMK administrators, and strengthening customer’s protection by providing the dispute resolution mechanism of non performing loan through Banking Mediation, Customer’s Complaints, the transparancy of Information and The Use of Customer’s Personal Data, until tightening the license of debtcollectors and the regulation of collecting ethics in which PBI and SEBI as the legal basis.